Improved Nutrition through Agricultural Extension and Advisory Services: Case studies of Curriculum Review and Operational Lessons from India - Babu, Suresh Chandra; Singh, Meera; Hymavathi, T. V.; Rani, Uma; Kavitha, G.G.; Karthik, Shree (World Bank, 2017)
Even after several decades of green revolution, malnutrition continues to be a major development challenge in much of South Asia, and India has a major share of the malnourished people in the region. The nutritional issues in India are complex and therefore require a multifaceted, multidisciplinary solution. One facet of the solution is increasing knowledge about the causes of and solutions to malnutrition at the farm household level through agricultural extension. Disseminating nutrition-sensitive agricultural knowledge is not currently an activity of agricultural extension in India, but there is great potential for integrating it through the well-established network of extension officers. For nutrition goals to be integrated into extension, the curricula provided to current and future agricultural extension agents must be revisited. As part of the South Asia Food and Nutrition Security Initiative (SAFANSI), this paper focuses on approaches to incorporating such nutrition content into the agricultural extension curriculum. Three state agricultural universities in Tamil Nadu, united Andhra Pradesh, and Bihar were used as case studies for the curriculum review. Through these case studies, face-to-face consultations at the national level down to program implementation at the village level have been developed. These include consultative workshops, and a conceptual framework and strategy for incorporating nutrition into extension curriculum development to improve nutrition outcomes. This strategy, detailed in this report, includes opportunities for collaboration from the national level to the community level. Specific lessons and follow-up actions are outlined that may be useful for other South Asian countries.